2013
DOI: 10.4103/0301-4738.119435
|View full text |Cite
|
Sign up to set email alerts
|

Causes and characteristics of work-related eye injuries in western Turkey

Abstract: Objectives:To analyze descriptive data and characteristics of work-related eye injuries (WREI) admitted into the emergency department (ED) and obtain information to utilize in planning measures to prevent WREI.Materials and Methods:This prospective study recruited patients with WREI admitted to the center in the two-year study period. Only the casualties occurred at the workplace and while working constituted the sample. The data were collected via face-to-face contact in the ED.Results:Males comprised the maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 15 publications
(30 reference statements)
6
35
2
Order By: Relevance
“…The large majority was unilateral, with a similar proportion of right/left eye involvement: this is in agreement with results of other studies [2,6]. Male workers are most frequently involved (87% vs. 13% in women), as previously reported [2,16,17]. This is not unexpected, considering the larger proportion of male workers traditionally engaged in high risk activities.…”
Section: Discussionsupporting
confidence: 92%
“…The large majority was unilateral, with a similar proportion of right/left eye involvement: this is in agreement with results of other studies [2,6]. Male workers are most frequently involved (87% vs. 13% in women), as previously reported [2,16,17]. This is not unexpected, considering the larger proportion of male workers traditionally engaged in high risk activities.…”
Section: Discussionsupporting
confidence: 92%
“…In most previous studies, the majority of patients referring to the ocular emergency units were in this age range (2, 9, 11, and 15). Individuals perform the majority of their occupational and professional activities over the age of 30; therefore, it is predictable that most occupational injuries, such as ocular injury, occur in this age range (16). In the present study, the most common emergency was OFB with the prevalence of 91.4%.…”
Section: Discussionmentioning
confidence: 69%
“…It has been reported that, in Turkey, WREI are more common among workers in metal work and machinery industries (2). The most common cause of eye injuries are due to corneal foreign bodies (5,6,18).…”
Section: Discussionmentioning
confidence: 99%
“…Social Security statistics indicate that the incidence of work-related injuries in Turkey is between 70,000 and 80,000 (2). More than 1.3 million work-related injuries that caused at least one day of loss of the workforce were reported in the United States, of which 36,680 of the work-related injuries were eye injuries (3).…”
Section: Introductionmentioning
confidence: 99%